The Some Issues of Law, Legal Gap, Morality, Happiness and Well-Being - Ononchimeg, Ryenchindorj (Advances in Social Sciences Research Journal, 2025)
The main goal of our study is to identify the focal points of state policy necessary to establish a stable and coherent legal system characterized by minimal gaps, overlaps, conflicts, and errors. Drawing on the country’s long history of statehood and intellectual heritage, the study emphasizes the intrinsic link between legal stability and effective state governance. Law is understood as a universally binding system rooted in the collective will of society, functioning through both written legislation and dynamic state authority to maintain social order, justice, and protect fundamental rights. While legal gaps are inevitable, they highlight the critical need for continuous legislative review and judicial intervention to uphold fairness and clarity. Also explores how morality often influences behavior more strongly than formal legal legitimacy, particularly in cultures with deep-rooted social values. Recognizing well-being as a multidimensional concept encompassing physical, psychological, social, and economic factors, the research advocates for culturally sensitive policies supported by robust legal frameworks. Integrating law, morality, and well-being through education, cultural respect, and legal reform is essential to promote harmonious, just, and flourishing communities.